DESAIN DAN ANALISIS SISTEM PENDINGIN KAPAL TRADISIONAL PENANGKAP IKAN 30 GT PANTAI UTARA LAMONGAN - Dimas Bayu Aji S; M Anis Mustaghfirin; Benedicta Dian Alfanda (Politeknik Perkapalan Negeri Surabaya, 2023)
There are several methods to cool fishermen's catches, namely the full ice blockmethod, the full refrigeration system method, and the combined ice method andrefrigeration system. Among these methods, the full ice block method is the most commonlychosen method by traditional fishermen because the use of this method is consideredcheaper than other methods. However, in terms of the quality of the fish cooled by thismethod, it is lacking., In this study a calculation of the cooling load of the hold is carriedout which will produce a cooling system using RSW (Refrigerated Seawater) with thesoftware method and will produce a suitable RSW design for the Ijon-in fishing boat hold.In addition, the calculation of the economic aspects of the use of RSW will be carried outcompared to conventional systems. The results of this study found that the coolingrequirement for the hatch was 10.9847064 Kw, therefore the compressor used had acooling capacity of 13.35 kW. Then we get a condenser design with a shell diameter of 350mm and a tube diameter of 25.4 mm and an evaporator design with a shell diameter of 600mm and a tube diameter of 12.7 mm.